Theoretical study of structural, electronic, and magnetic properties of graphene with adsorbed palladium and vanadium based on density functional theory - Abdullahi, Yusuf Zuntu (2013)
Graphene possesses interesting properties projected for various potential applications. The accurate understanding of how these properties are affected by the introducing foreign nanostructures into the sheet particularly transition metals (TM) has received the most attention. It is necessary to use theoretical method based on quantum mechanics to study the properties of graphene system with adsorbed metallic nanostructures. This thesis employs first principles calculations based on density functional theory implemented in the QUANTUM ESPRESSO simulation package to investigate the stable geometries and electronic and magnetic properties of graphene with adsorbed transition metals (palladium Pd and vanadium V). The calculations are performed using ultrasoft pseudopotential and Perdew-Burke- Enzerhof (PBE) generalized gradient approximation (GGA) exchange-correlation functionals. For Brillouin zone (BZ) integrations, 8×8×1 set of k-points is sampled using Mankhorst-Pack scheme. In modeling a graphene sheet, 4×4×1 supercell containing 32 carbon atoms is constructed in a 3-dimensional periodic boundary conditions with 2.46 Å in plane lattice constant. Plain-wave basis with the kinetic energy cut-off of 500 eV is used to expand the wave functions. The structural optimizations of various configurations considered are performed to allow the structures to relax based on force and energy minimization. For the adsorption of Pd adatom and dimer, the results show significant covalent bonding with the graphene sheet. The density of states reveals that the system is semiconducting and metallic at low coverage adsorption of Pd adatom and dimer respectively. Moreover, it is found that Pd-Pd bond length is much weakened compared to an isolated Pd dimer with nearly symmetric height above the adsorption sites indicating that linear coverage can be achieved. For adsorption of vanadium atoms, the findings show that the system is metallic and magnetic. The stable vanadium dimer configuration which has not been reported in the previous works has shown little enhancement of magnetic moment per unit cell compared to isolated dimer whereas single V adatom adsorption has magnetic moment value per unit cell far more than that of an isolated V atomic value of 3μB. The orbital proportion in bonding between vanadium and carbon (C) is examined based on calculated projected density of states (PDOS). It is found that pz of C is dominated by the spins states even at the vicinity of Fermi level and partial contribution from d orbital of V was also observed. This trend of orbital contributions appears to be uniform even for Pd atoms adsorption on graphene.